Design and Synthesis of 56 Shape‐Diverse 3D Fragments. Issue 41 (8th July 2020) - Downes, Thomas D.; Jones, S. Paul; Klein, Hanna F.; Wheldon, Mary C.; Atobe, Masakazu; Bond, Paul S.; Firth, James D.; Chan, Ngai S.; Waddelove, Laura; Hubbard, Roderick E.; Blakemore, David C.; De Fusco, Claudia; et al.
Abstract: Fragment‐based drug discovery is now widely adopted for lead generation in the pharmaceutical industry. However, fragment screening collections are often predominantly populated with flat, 2D molecules. Herein, we describe a workflow for the design and synthesis of 56 3D disubstituted pyrrolidine and piperidine fragments that occupy under‐represented areas of fragment space (as demonstrated by a principal moments of inertia (PMI) analysis). A key, and unique, underpinning design feature of this fragment collection is that assessment of fragment shape and conformational diversity (by considering conformations up to 1.5 kcal mol −1 above the energy of the global minimum energy conformer) is carried out prior to synthesis and is also used to select targets for synthesis. The 3D fragments were designed to contain suitable synthetic handles for future fragment elaboration. Finally, by comparing our 3D fragments with six commercial libraries, it is clear that our collection has high three‐dimensionality and shape diversity. Abstract : Thinking in 3D : 56 3D (rather than sp 3 ‐rich) disubstituted pyrrolidine and piperidine fragments were designed and synthesised. Computationally generating global minimum energy and higher‐energy (but accessible) conformers of potential 3D fragments and assessing their shape by principal moments of inertia analysis prior to synthesis ensured that the collection was significantly three‐dimensional and shape diverse, as demonstrated by comparison with six commercial fragment libraries.